Strategi Komunikasi Kelompok Kesenian Wahyu Turonggo Seto Dalam Menyampaikan Informasi - Munawaroh, Atik; Wasisto, Joko (UPT Perpustakaan Universitas Semarang, 2022)
This study aims to find out and understand how the communication strategy used by the Wahyu Turonggo Seto art group in conveying information both to its members and to the public. This study uses 3 methods, observation, interviews, and documentation. The data analysis technique uses the steps according to Miles and Huberman, namely data collection, data reduction, data presentation, to drawing conclusions. There are 4 informants, namely art group managers, art group members, art lovers, and the general public. The results of the study show that the communication strategy carried out by the Wahyu Turonggo Seto art group is by using wara-wara directly and indirectly, such as through social media. The use of this strategy is said to be effective because people are already using digital applications as an effort to meet their information needs. The obstacles faced by the Wahyu Turonggo Seto art group are that there are some members who are old and do not have gadgets to receive information related to schedules and other matters related to the arts group.